Opportunities of Young Fish Farmers in Indigenous Fish Farming: A village level study - Iffat Ara Mahzabin; Sabicun Nahar; Mst Sharmin Akter (Research in Agriculture Livestock and Fisheries, 2024)
Bangladesh is a country enriched with diverse fisheries resources and naturally productive wetlands. Indigenous fish plays an important role in diet and also a source of income for fish farmers. The main aim of the study was to determine the extent of opportunities for young fish farmers in indigenous fish farming. Melandah upazila under Jamalpur district was the locale of the study. The sample size of the study was 80 and it was drawn from a population of 266 using a simple random sampling technique. Data were collected from the selected sample farmers through face-to-face interview methods during 1-30 January 2023. The extent of opportunity was the dependent variable and a 4-point rating scale was used to measure it, while eleven selected characteristics of the respondents constituted the independent variables of the study. Pearson’s Product Moment Correlation Coefficient (r) was computed to explore the relationship between the selected characteristics of the respondents. The findings revealed that more than three-fourths of the young fish farmers (78.8%) had adequate opportunities in indigenous fish farming. Transportation facilities came in first place among issues pertaining to opportunities, followed by locally available good-quality feed and fertilizers, which came in second and third, respectively. Age, experience in raising fish, annual family income, training exposure, contact with extension media, knowledge of indigenous fish farming, and skills in indigenous fish farming were all found to be significant influences on the extent of opportunities in indigenous fish farming. The Department of Fisheries and other development organizations should take the required steps to increase young fish farmers’ opportunities to engage in indigenous fish farming and contribute to the national economy. Vol. 10, No. 3, December 2023: 293-300